Recontruction of the Decline of Clasiccal Islamic Libraries During the Umayyad Daulad Period (680-750 H) - Siti Mutmainah, Ella Oktaviani, Irva Yunita, (Jurnal El-Pustaka, 2024)
History covers the journey of human life in filling the world's development from time to time. Every history has meaning and value, so that humans can make their own history and history shapes humans. This research aims to analyze how the decline of Islamic libraries during the time of the Ummayah leadership in the Islamic context moved away from text traditions and context. The text tradition is earlier than the context tradition, which can be traced through the Islamic religious tradition. To study or examine a religion, there are at least five forms of religious symptoms that need to be considered, including literary texts that provide teaching sources. Islamic libraries are part of an Islamic civilization that emerged and experienced development since the beginning of Islam, namely during the prophetic period, the Khulafa al-Rashidin era, and during the Islamic daulahs. If we look at it in a historical context, the development of Islamic libraries experienced a significant increase during the daulahs, so this article focuses on the development of Islamic libraries during the Umayyad Daulah era. This is considered important because apart from the caliphs at that time being directly involved or contributing greatly to the development of libraries, there were caliphs who contributed or had a big role in it, as well as the factors that caused the decline of Islamic libraries, so that this becomes interesting to study exploratively with a historical approach. The decline and vacuum in the Islamic world began with the fall of Muslim regions after physical war against their enemies, and also among the Muslim community itself. Apart from human factors, the destruction of Islamic libraries was also caused by natural phenomena, such as earthquakes. There needs to be a collective awareness for society to reconstruct their thinking that progress cannot be achieved without mastery of science.